2004
DOI: 10.1093/rheumatology/keh392
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in Italian patients with systemic lupus erythematosus. II. Role of clinical, immunological and psychological determinants

Abstract: Anxiety, depression and joint pain seem to be the major determinants of HRQOL impairment in SLE patients. Damage seems to influence HRQOL mostly through depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
90
2
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 24 publications
14
90
2
6
Order By: Relevance
“…In agreement with the present findings, Doria et al reported that with increasing age, SLE patients obtained lower scores in the physical and mental dimensions of QoL (10). In addition, Elhone et al performed a study on QoL in lupus patients during 15 years and concluded that age was negatively associated with QoL, especially the physical dimension (11).…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with the present findings, Doria et al reported that with increasing age, SLE patients obtained lower scores in the physical and mental dimensions of QoL (10). In addition, Elhone et al performed a study on QoL in lupus patients during 15 years and concluded that age was negatively associated with QoL, especially the physical dimension (11).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have identified psychosocial (e.g., social support) and behavioral variables (e.g., helplessness, coping with illness) as being associated with quality of life in patients with SLE (7)(8)(9)(10)(11). However, inconsistent results have been reported regarding the influence of disease activity and damage on quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of assessing HRQL in patients with chronic pain has been documented by our recent studies of patients with inflammatory rheumatic diseases (RA, psoriatic arthritis and ankylosing spondylitis) (70), systemic lupus erythematosus (81,82), symptomatic knee and hip osteoarthritis (69), postmenopausal women with vertebral fractures (83), and fibromyalgia (59). In comparison with healthy controls, all of the rheumatic conditions significantly impaired all eight health concepts of the SF-36 in both the physical and mental component, but the disease with the worst HRQL for these dimensions was RA (70).…”
Section: Health-related Quality Of Life Assessmentmentioning
confidence: 99%
“…In comparison with healthy controls, all of the rheumatic conditions significantly impaired all eight health concepts of the SF-36 in both the physical and mental component, but the disease with the worst HRQL for these dimensions was RA (70). Overall, the dimensions typically affected in inflammatory rheumatic diseases were physical functioning, limitations due to physical function, and bodily pain, whereas the level of perceived HRQL in patients with fibromyalgia seems to be explained more by their mental health than by their physical condition (59,69,70,(81)(82)(83). A number of pain-related quality of life selfadministered instruments have been constructed to evaluate pain-related functional disturbances in specific diseases or pain conditions in which the patient is asked to list the activities or tasks they regularly performed before the onset of pain but have since found difficult.…”
Section: Health-related Quality Of Life Assessmentmentioning
confidence: 99%